Counter-Measures against Stack Buffer Overflows in GNU/Linux Operating Systems - Leon, Erick; Bruda, Stefan D. (Procedia computer science, 2016)
We address the particular cyber attack technique known as stack buffer overflow in GNU/Linux operating systems, which are widely used in HPC environments. The buffer overflow problem has been around for quite some time and continues to be an ever present issue. We develop a mechanism to successfully detect and react whenever a stack buffer overflow occurs. Our solution requires no compile-time support and so can be applied to any program, including legacy or closed source software for which the source code is not available. This makes it especially useful in HPC environments where given their complexity and scope of the computing system, incidents like overflows might be difficult to detect and react to accordingly.